Ensuring Cybersecurity in the Modern World: Challenges from Artificial Intelligence-Based Fraud Posing a Threat to the Environment - Marko, Serhiy; Tsaruk, Yuriy; Skhidnytska, Halyna; Kryshtanovych, Myroslav; Nikonenko , Uliana (Journal of Ecohumanism, 2024)
Cybersecurity in the modern world is a critical field that involves protecting systems, networks, and programs from digital attacks. With advancements in technology, artificial intelligence (AI) has become a double-edged sword. While AI can enhance cybersecurity measures, it also introduces new vulnerabilities. Fraudulent activities facilitated by AI not only pose risks to financial and data security but increasingly threaten environmental sustainability as well. The purpose of the article is to identify ways to ensure cybersecurity. The object of the study is challenges from fraud using artificial intelligence technologies that threaten the environment. The research methodology involves the use of modern IDEF0 modeling methods. As a result of the study, a model for ensuring cybersecurity is presented.